Antibacterial and antioxidant properties of shorea sumatrana leaves / Tazkeerah Hasanah Awang Said - Awang Said, Tazkeerah Hasanah (Faculty of Applied Sciences, 2015)
The timber value of Shorea sumatrana has been well known from decades. Shorea is a major exotic species found in tropical regions and they are one of the endemic plants in Malaysia. This study is aimed to evaluate the antibacterial and antioxidant properties of the methanol extract of Shorea sumatrana leaves. The antibacterial activity of the methanol extract of S. sumatrana was assessed against gram-positive and gram-negative bacteria by disc diffusion method. On the other hand, the antioxidant activity was detected by DPPH radical scavenging activity. In the preliminary screening experiment of antibacterial activity, all of the tested bacteria showed varying degrees of sensitivity to the leaves extracts excluding P. aeruginosa. Results obtained that S. epidermidis, a gram-positive bacterium as the most susceptible to the extracts of leaves at the applied doses. Besides, only P. aeruginosa was resistant to the extracts. My findings clearly demonstrate that the leaves extracts of S. sumatrana had strong antibacterial effects and raises the possibility of using the extracts as antibacterial agents in treating pathological conditions caused by bacteria infection. Although the effect of S. sumatrana leaves against some pathogenic bacteria in vitro is promising, further microbiological and pharmacological studies will be required. In present study, in vitro antioxidant activities of the methanolic extracts of leaves of S. sumatrana were determined by spectrophotometric methods. Antioxidant activities of extract were expressed as percentage of DPPH radical inhibition. The methanolic extract of S. sumatrana leaves showed maximum antioxidant activity of 98.87% at 500 pg/ml concentration. Thus, this study reveals that leaves of S. sumatrana has a potential as a natural sources of antioxidant.